1974
DOI: 10.1111/j.1365-2222.1974.tb01390.x
|View full text |Cite
|
Sign up to set email alerts
|

Munchausen's stridor: non‐organic laryngeal obstruction

Abstract: Summary A patient had at least 15 hospital admissions for symptoms of acute dyspnoea accompanied by loud stridorous sounds. These episodes had been diagnosed as acute airway obstruction and she was treated on all occasions on an emergency basis. In the absence of a definitive etiology and with other clues, it was then recognized that the patient was imitating the clinical appearance of laryngeal obstruction. Following the establishment of this, psychiatric care was initiated with the goal of rehabilitation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
99
0
3

Year Published

1987
1987
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(102 citation statements)
references
References 1 publication
0
99
0
3
Order By: Relevance
“…The first modern case report was published by PATTERSON et al [3] in 1974 who demonstrated laryngoscopic evidence of VCD, which he termed ''Munchausen's stridor''. In 1983 CHRISTOPHER et al [4] published a seminal paper that described a group of patients evaluated for severe asthma who were found to have VCD.…”
Section: Historical Perspectivementioning
confidence: 99%
“…The first modern case report was published by PATTERSON et al [3] in 1974 who demonstrated laryngoscopic evidence of VCD, which he termed ''Munchausen's stridor''. In 1983 CHRISTOPHER et al [4] published a seminal paper that described a group of patients evaluated for severe asthma who were found to have VCD.…”
Section: Historical Perspectivementioning
confidence: 99%
“…The earliest portrayals of VCD were based mainly on case reports and small series. Earlier belief considered VCD as a psychological illness, a factitious entity, a hysterical neurosis or a somatoform disorder with "a loss of or alteration in physical functioning" [8,[31][32][33][34]. Supposedly, unnamed stressors or an unidentified disturbance in both patient and family play significant roles in VCD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Eur Respir J., 1995Respir J., , 8, 1978Respir J., -1981 Vocal cord dysfunction secondary to psychogenic factors (PVCD) was first recognized in 1974, presenting as organic upper airways obstruction [1]. Presentations with a picture simulating bronchial asthma were later described.…”
Section: P Ps Sy Yc Ch Ho Og Ge En Ni Ic C V Vo Oc Ca Al L C Co or Rdmentioning
confidence: 99%